Statistical analysis of vehicle accidents in the city of Ibarra over the period 2017-2022 - Santana , Carlos; Maldonado, Anthony; Cabascango, Fabio; Guerrero, Bryan; Quelal, Gabriel; Gamez, Brizeida (EASI: Engineering and Applied Sciences in Industry, 2023)
A relevant fact in the city of Imbabura is the result of traffic accidents. In some of these events people are reported injured and in extreme cases deceased. This situation should be minimized in order to avoid consequences. In pedestrians, drivers and the community in general. Considering the above, it is important to identify the causes of traffic accidents in the city, by performing a detailed analysis of the factors that influence the occurrence of these events. For this purpose, the analysis of statistical data obtained in the period 2017-2022 by the state entities, for traffic accidents considering the main data carried out at the time the accidents happen, is exposed. The qualitative method was chosen to obtain conclusions from heterogeneous and unstructured data that are not detailed numerically. Based on the information collected, human factors were identified as key elements, specifically alcohol consumption, speeding and disrespect for traffic regulations. With respect to the areas of the city with the highest number of accidents, it was determined that they correspond to the areas surrounding the Amazonas Market and the Stadium; while the highest incidence of accidents occurs on weekends.